2014
DOI: 10.1016/j.expthermflusci.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal two-phase flow pattern recognition

Abstract: In the present work a Wire Mesh Sensor (WMS) has been adopted to characterize the air-water two-phase flow in a test section consisting of a horizontal Plexiglas pipe of internal diameter 19.5 mm and total length of about 6 m. The flow quality ranges from 0 to 0.73 and the superficial velocity ranges from 0.145 to 31.94 m/s for air and from 0.019 to 2.62 m/s for water. The observed flow patterns are stratified-bubble-slug/plugannular. The WMS consists of two planes of parallel wire grids (16x16) that are place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The results also indicated that heat transfer coefficient increased with increasing predominant frequency. Many other authors reported further important results related to the analysis of frequencies present in pressure and flow pattern fluctuations (Lee et al (2018), O'Neil et al (2018, Ma et al (2018), Monni et al (2014)).…”
Section: Introductionmentioning
confidence: 93%
“…The results also indicated that heat transfer coefficient increased with increasing predominant frequency. Many other authors reported further important results related to the analysis of frequencies present in pressure and flow pattern fluctuations (Lee et al (2018), O'Neil et al (2018, Ma et al (2018), Monni et al (2014)).…”
Section: Introductionmentioning
confidence: 93%
“…The complexity of multiphase flow originates from its variable and fluctuating phase interface, , and the conservation of dynamics at the phase interface leads to changes in the flow structure in time and space. The oil–gas–water flow, which is a kind of gas–liquid–liquid three-phase flow, can also be considered as a special type of gas–liquid two-phase flow .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the research focused on two-phase flow with the WMS technique has been growing (Assima et al, 2015; Kanai et al, 2012; Puchtler et al, 2015; Vieira et al, 2014b; Zhang et al, 2013). As a multi-points measurement technique, WMS not only measures and visualizes local and cross-sectional flow parameters (Abdulahi and Azzopardi, 2014; Barnea et al, 2013; Petritsch et al, 1997), but can also be used for flow process characterization and flow pattern recognition (Monni et al, 2014).…”
Section: Introductionmentioning
confidence: 99%